Pemberdayaan Masyarakat melalui Pemanfaatan Botol Bekas di Desa Depok Desa Depok Kecamatan Darangdan Purwakarta - Narkum; Aulia, Vika Husnul; Wulandari, Dyah (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
The accumulation of rubbish is also due to a lack of public awareness in disposing of rubbish in its proper place. Community empowerment is an effort to make people recognize themselves. Community empowerment is an effort to develop one's abilities freely while simultaneously overcoming the waste problem through the management of used goods. The form of activity carried out is going directly to the field on Sunday, February 25 2024 in Depok Village, Darangdan District. Before implementing empowerment, it goes through three stages: 1. Observing each RW regarding waste problems 2. Providing explanations about waste and waste management to residents 3. Implementing community empowerment activities by using used bottles. Community empowerment through waste management can help the economy if carried out sustainably and continuously upgrading these crafts. . With this service, the community can be more aware of the classification of waste and the value of used goods if they are managed into crafts. Of course, making flower crafts from used bottles will also reduce waste generation. The targets in this community empowerment activity include SD Negeri 1 Depok, SD Negeri 2 Depok, SMP Negeri 6 Darangdan, and cadre mother